Edukasi Pembuatan Pupuk Organik: Solusi Alternatif Mengatasi Kelangkaan Pupuk Bagi Petani Desa Senanggalih - Lalu Azikri Amrullah; Mardiyan Dwi Saputra; Alza Safira; Irnia Anggilia; Sri Mulyawati (Indonesian Journal of Education and Community Services, 2026)
The scarcity and high price of subsidized fertilizers have become major obstacles to farmer productivity in Senanggalih Village. This study aims to educate the community on organic fertilizer production as an independent alternative solution by utilizing local waste. The method used was participatory training (learning by doing) involving 20 representatives of farmers and livestock breeders from each hamlet on January 19, 2026. The activity stages included theoretical socialization, practical demonstrations using livestock manure, burnt husks, EM4, and molasses, as well as an evaluation stage. The results showed a paradigm shift among farmers in viewing organic waste and an improvement in technical skills regarding the fermentation process. Based on evaluation data from questionnaires, this program achieved a very high level of satisfaction (100% on the agree and strongly agree scales) across all success indicators. In conclusion, this education is effective in increasing farmer independence and providing a concrete solution to the dependency on chemical fertilizers in Senanggalih Village.